Cardiovascular sudden death and its progression between cross-disciplinarity and cross-sectorial approach - Luis A. Ochoa Montes; Rafael E. Araujo González; Daisy Ferrer Marrero (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Due to its high incidence, the dramatics which accompanies its presentation and because it is an important cause of potentially lost years of life, sudden death represents a challenge at present. The complexity of its physio-pathologic elements, and the diversity of the population groups in which it takes place demand a cross-discipline study. It is necessary to abandon positions and trends which center cardiovascular sudden death in a single medical specialty, mainly with regards to its causes, since it is an entity which requires an integrated vision from the different specialties and levels of attention.